2012
DOI: 10.1371/journal.pgen.1003092
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitylation Machinery Is Required for Embryonic Polarity in Caenorhabditis elegans

Abstract: The Caenorhabditis elegans one-cell embryo polarizes in response to a cue from the paternally donated centrosome and asymmetrically segregates cell fate determinants that direct the developmental program of the worm. We have found that genes encoding putative deubiquitylating enzymes (DUBs) are required for polarization of one-cell embryos. Maternal loss of the proteins MATH-33 and USP-47 leads to variable inability to correctly establish and maintain asymmetry as defined by posterior and anterior polarity pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Surprisingly, while multiple Ub'n enzymes (E1, E2, and E3) are essential in yeast (6 -8), only a single DUB is essential for viability of both budding and fission yeasts (6 -11), suggesting that considerable functional overlap may exist in yeast under standard laboratory conditions. In contrast, in metazoans, knockdown or loss of individual DUBs often results in developmental defects or disease states (3,12,13). Consistent with this possibility, we previously found that loss of five DUBs (5DUB delete: ubp4⌬1 ubp5⌬ ubp9⌬ ubp15⌬ sst2⌬) but not any combination of four intracellular membrane trafficking DUBs significantly impacted cell polarity, Ub conjugate accumulation, and viability in S. pombe (1).…”
supporting
confidence: 61%
“…Surprisingly, while multiple Ub'n enzymes (E1, E2, and E3) are essential in yeast (6 -8), only a single DUB is essential for viability of both budding and fission yeasts (6 -11), suggesting that considerable functional overlap may exist in yeast under standard laboratory conditions. In contrast, in metazoans, knockdown or loss of individual DUBs often results in developmental defects or disease states (3,12,13). Consistent with this possibility, we previously found that loss of five DUBs (5DUB delete: ubp4⌬1 ubp5⌬ ubp9⌬ ubp15⌬ sst2⌬) but not any combination of four intracellular membrane trafficking DUBs significantly impacted cell polarity, Ub conjugate accumulation, and viability in S. pombe (1).…”
supporting
confidence: 61%
“…The effect of math-33 inactivation on the Psod-3::GFP reporter activity was further analyzed using the math-33(tm3561) allele, which has been previously characterized as a loss-of-function allele in the context of early embryonic polarity establishment (McCloskey and Kemphues, 2012). In our experiments, math-33 inactivation by the loss-of-function math-33(tm3561) allele in daf-2(e1370) nematodes reduced Psod-3::GFP reporter activity to a level similar to that observed in daf-16(mu86); daf-2(e1370) control animals (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this idea, USP-46 and its homologs have been shown to function together with other DUBs in several systems. USP-46 functions together with USP-47 and MATH-33/USP7 to regulate cell polarity in the C. elegans embryo (26), and the USP46 homolog Ubp9 functions redundantly with several other DUBs to regulate endocytosis and cell polarity in S. pombe (24) and mitochondrial function in S. cerevisiae (23). Further genetic and biochemical analysis will be required to identify the usp-46-independent mechanisms by which the WDR proteins regulate GLR-1.…”
Section: Discussionmentioning
confidence: 99%
“…USP-46 and its homologs have been implicated in regulating diverse cellular functions, including endocytosis, cell polarity, signal transduction, chromatin modification, and mitochon-drial biogenesis (22)(23)(24)(25)(26)(27). In some cases, the substrates of the DUB have been identified.…”
mentioning
confidence: 99%